RASIO KEUANGAN SEBAGAI ALAT PREDIKTOR DELISTING PERUSAHAAN Financial ratio, delisting, listing dan discriminant analysis - Nurhidayati Nurhidayati; sofyan S Harahap (Universitas Trisakti, 2004)
The objective of the paper is to discuss the role of financial ratios as a tool of prediction of delisted companies. The following Financial Rasio are used: Earning per share, Equity per sahre, Closing price, Price eaming ratio, Price to book value, Debt to equity ratio, Current ratio, Net profit Margin and Retum on Asset. Sampel consists of 36 financial statements of delisted companies 1995 to 2002 and 45 fincial statements of isted companies at Jakarta Stock Exchange in 2002. The Statistical model used discrimant analysis with significantrate of a 5%. Debt to equity ratio and Net profitmargin are themosts listing and delisting companies. The validity of this model to predict the listed and delisted companies is 79,2%. ntratios that distinguish between.